Lenticulostriatal ischemia shows relevant SSTR expression on PET/CT imaging using the novel SSTR-targeting peptide 18F-SiTATE: interesting images - Kunte, Sophie Carina; Unterrainer, Lena M.; Kunz, Wolfgang G.; Winkelmann, Michael; Lindner, Simon; Jurkschat, Klaus; Wängler, Carmen; Wängler, Björn; Schirrmacher, Ralf; Bartenstein, Peter; Belka, Claus; Schichor, Christian; et al. (Clinical nuclear medicine, 2024)
A 64-year-old woman with meningioma presented with left-sided lenticulostriatal ischemia following craniotomy and debulking of a sphenoid wing meningioma. For subsequent radiotherapy planning, an SSTR-targeted PET/CT using the novel ligand 18F-SiTATE was performed 2.5 months thereafter. The meningioma remnants showed transosseous, intrasellar, and perivascular extension around the internal carotid artery with strong SSTR expression. Moreover, there was focal 18F-SiTATE uptake in the left caudate and corresponding contrast enhancement due to postischemic blood-brain barrier disruption and reactive SSTR expression. Therefore, increased cortical or subcortical SSTR PET signal may be related to ischemic changes even in the subacute stage after initial stroke.
Im Titel ist die Zahl 18 hochgestellt
Gesehen am 14.04.2025